Emergency care of patients receiving non-vitamin K antagonist oral anticoagulants. (April 2018) - Eikelboom, J.W.; Kozek-Langenecker, S.; Exadaktylos, A.; Batorova, A.; Boda, Z.; Christory, F.; Gornik, I.; Kėkštas, G.; Kher, A.; Komadina, R.; Koval, O.; Mitic, G.; et al.
Abstract: Non-vitamin K antagonist oral anticoagulants (NOACs), which inhibit thrombin (dabigatran) and factor Xa (rivaroxaban, apixaban, edoxaban) have been introduced in several clinical indications. Although NOACs have a favourable benefit-risk profile and can be used without routine laboratory monitoring, they are associated–as any anticoagulant–with a risk of bleeding. In addition, treatment may need to be interrupted in patients who need surgery or other procedures. The objective of this article, developed by a multidisciplinary panel of experts in thrombosis and haemostasis, is to provide an update on the management of NOAC-treated patients who experience a bleeding episode or require an urgent procedure. Recent advances in the development of targeted reversal agents are expected to help streamline the management of NOAC-treated patients in whom rapid reversal of anticoagulation is required.